Características del clima escolar en niños de la tercera infancia - Hincapie Cardona, Johanna Alexandra (Universidad Antonio Nariño, 2021)
In third childhood, peer relationships become very important; the relationship with them, and the environment in general that they live in this stage of development, because this is where links are established; An example of this is that schools are changing, so that their organizations, classrooms, practices, and relationships are becoming increasingly complex, as teachers and students have the possibility to participate, expressing their preferences, feelings and expectations in communication spaces. The objective of the present investigation was to identify the characteristics of the school climate from the relational, educational, belonging, justice and security dimensions in children of the third childhood. It was aimed at fourth grade students of the San Simon de Ibague educational institution, applied to the Restrepo and Montealegre headquarters, aged between 8 and 12 years; It was evidenced that the evaluated students present a perception of the school climate located in medium risk, it was evidenced that the children between the ages of 11 and 12, have a slightly more negative perception of the school climate; which implies a need for improvement in this area in the institution